Image-Guided Injections of the Hip - Evren Yasar; Jaspal R Singh; John Hill; Venu Akuthota (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2014)
The authors present a technique paper on the utilization of both ultrasound and fluoroscopy guidance for injections about the hip joint.  This review draws from specialists including physiatry, family medicine and orthopaedic surgery.  We hope the editors and reviewers find this document beneficial to the readership, especially those practicing musculoskeletal medicine and may use this information when performing hip injections.